Characterization of a Novel WDR5-binding Site That Recruits RbBP5 through a Conserved Motif to Enhance Methylation of Histone H3 Lysine 4 by Mixed Lineage Leukemia Protein-1 - Odho, Zain (American Society for Biochemistry and Molecular Biology, 2010)
Histone modification is well established as a fundamental mechanism driving the regulation of transcription, replication, and DNA repair through the control of chromatin structure. Likewise, it is apparent that incorrect targeting of histone modifications contributes to misregulated gene expression and hence to developmental disorders and diseases of genomic instability such as cancer. The KMT2 family of SET domain methyltransferases, typified by mixed lineage leukemia protein-1 (MLL1), is responsible for histone H3 lysine 4 methylation, a marker of active genes. To ensure that this modification is correctly targeted, a multiprotein complex associates with the methyltransferase and directs activity. We have identified a novel interaction site on the core complex protein WD repeat protein-5 (WDR5), and we mapped the complementary site on its partner retinoblastoma-binding protein-5 (RbBP5). We have characterized this interaction by x-ray crystallography and show how it is fundamental to the assembly of the complex and to the regulation of methyltransferase activity. We show which region of RbBP5 contributes directly to mixed lineage leukemia activation, and we combine our structural and biochemical data to produce a model to show how WDR5 and RbBP5 act cooperatively to stimulate activity.